The Nexus Between Green Banking, Governance Quality, and Financial Performance: Evidence from the Islamic Banking Sector in Indonesia - Wijanegara, Anggita Saraswati; Amalia, Putri Syifa; Aldrian, Mochamad Ridwan (Tazkia Islamic University College, 2026)
This study investigates the impact of Green Banking Disclosure and Good Corporate Governance (GCG) mechanisms on the financial performance of Islamic commercial banks in Indonesia. A quantitative approach was employed using secondary data from annual and sustainability reports of 12 Islamic Commercial Banks registered with the Financial Services Authority (OJK) between 2021 and 2023. Data analysis was conducted using panel data regression. The results demonstrate that Green Banking Disclosure has a positive and statistically significant effect on financial performance, suggesting that environmental transparency serves as a strategic driver for profitability. Conversely, the independent board of commissioners exhibits a negative and significant influence on ROA. Furthermore, both the audit committee and the Sharia Supervisory Board were found to have negative but statistically insignificant effects on financial outcomes. These findings underscore that substantive sustainability initiatives generate stronger market legitimacy and financial value compared to mere structural compliance with governance requirements. The study suggests that Islamic banks should prioritize the integration of green banking practices into their core strategies while ensuring that governance structures are optimized for strategic expertise rather than formalistic monitoring.